An Improved Translation of SA/RT Specification Model to High-Level Timed Petri Nets - Nixon, Patrick (Trinity College Dublin, Department of Computer Science, 1995)
Structured analysis methods for real-time systems (SA/RT) are widely accepted by the industrial world as a mature approach to real-time systems design. These methods use highly expressive graphical specification languages to specify system requirements. Giving semantics to SA/RT specifications via selected formal models has the advantage of not only retaining their user-friendly and problem-oriented characteristics, but also making good use of the existing results of formal models for easier simulation and more powerful analysis. An automatic translation from SA/RT specification models to high-level timed Petri nets has recently been reported in [5]. But this translation suffers from some drawbacks, especially that it is not compositional, and the resulting subnets, in some cases, can be of at least exponential complexity. In this paper, we propose an improved translation, which is compositional and the resulting nets are of much lower complexity, e.g. the number of transitions is linear with respect to the scale of the original model. The efficient translation will benefit the simulation and analysis of specifications, and the compositionality of the translation process will support their incremental or modular development and compositional analysis.
Keywords: Computer Science